2015
DOI: 10.1007/s10950-015-9487-y
|View full text |Cite
|
Sign up to set email alerts
|

The M w 4.3 January 17, 2014, earthquake: very rare seismic event on the Siberian platform

Abstract: Abstract:We have studied the structural geology and geomorphology of the fault zones in the junction area of the Angara-Lena uplift and the Predbaikalsky trough. We have analyzed faults and folds and reconstructed paleostresses for this junction area named the Irkutsk amphitheatre. Our study shows that syn-fold (Middle Paleozoic) faults include thrusts, reverse faults and strike-slip faults with reverse components, that occurred due to compression from the neighbouring folded region. Recently, contrary to comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
3

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 32 publications
0
1
0
3
Order By: Relevance
“…двух платформенных землетрясений (26.02.1996 г., К=11.6, и 17.01.2014 г., К=13.3 [Melnikova, Radziminovich, 1998;Seredkina et al, 2015]) позволяет за-ключить, что ось максимального горизонтального сжатия современного поля напряжений на уровне средней части коры в пределах Иркутского амфи-Рис. 14.…”
Section: разломная структура и поля напряжений в верхней части осадочunclassified
“…двух платформенных землетрясений (26.02.1996 г., К=11.6, и 17.01.2014 г., К=13.3 [Melnikova, Radziminovich, 1998;Seredkina et al, 2015]) позволяет за-ключить, что ось максимального горизонтального сжатия современного поля напряжений на уровне средней части коры в пределах Иркутского амфи-Рис. 14.…”
Section: разломная структура и поля напряжений в верхней части осадочunclassified
“…Механизмы очагов землетрясений по [Solonenko et al, 1993;Melnikova, Radziminovich, 1998;Seredkina et al, 2015] показаны проек-циями верхней полусферы. Цифрой 1 отмечен фокальный механизм землетрясения 26.02.1996 г.…”
Section: современное напряженное состояние земной коры юга сибирской unclassified
“…The earthquake focal mechanisms from [Solonenko et al, 1993;Melnikova, Radziminovich, 1998;Seredkina et al, 2015] are shown as the upper hemisphere projections. Earthquake focal mechanisms: 1 -26.02.1996 earthquake (K=11.6), 2 -17.01.2014 earthquake (K=13.3) that occurred within the Siberian platform.…”
Section: современное напряженное состояние земной коры юга сибирской mentioning
confidence: 99%
See 1 more Smart Citation